Tingimento de seda e lã com corante natural eucalipto - Silva, Márcia Gomes da (2013)
Coloration of the proteic fabrics takes place through dyeing processes, that means an adsorption process. Particularly, wool and silk are protein-based fibers that have a general formula NH2.CHR.COOH. Their molecules have various superficial groups, which determine the polymer properties. The most important of these groups for dyeing with acid dyes are COOH and NH2. Unfortunately, the process of dyeing protein fibers is very pollutant because synthetic dyes are generally recalcitrant substances. Even after the conventional treatment of coagulation/ flocculation sludge of low biodegradability is generated. In order to minimize the environmental impact, dyeing with natural colorants has been increasingly applied. Therefore, this study aimed to evaluate the dyeing process of wool and silk fabrics with natural dye obtained from the leaves of the eucalyptus tree (Eucalyptus grandis). It has been investigated the optimal experimental conditions for dyeing related to the parameters: pH, initial concentration of the dye solution and temperature. The influence of potassium alum as mordant in the wash fastness of dyed fabrics has been also investigated. It has been concluded that pH 3, the initial concentration of 20 g.L-1 and temperatures of 80 and 90 °C are conditions which produced the best adsorption results in the wool and silk, respectively. Such results have been used to investigate the dyeing kinetics and the dyeing process at equilibrium through adsorption isotherms. It was found by the kinetic study that the pseudo-second order equation is the one that best represents the kinetic mechanism of dyeing for both fabrics, which is related to the chemisorption process as the rate-controlling step. The equilibrium data for wool and silk fabrics were easily adjusted to the Langmuir-Freundlich model indicating the significant contribution of chemisorption process in a monolayer. The thermodynamic properties ΔH°, ΔG° and ΔS° were evaluated and showed that the adsorption of the eucalyptus dye on silk and wool is a spontaneous process, due to the values of Gibbs free energy. The enthalpy of adsorption was positive for silk dyeing, indicating that the process is endothermic and high entropy change. For the wool dyeing observed this same behavior in the temperature range between 70 and 80 °C, but the range of 80 to 90 °C the enthalpy was negative, showing that in this case the process is exothermic. The fastness properties of the wool and silk dyeing were not significantly altered with the mordant.